Analysis of the Chemical Content of Virgin Coconut Oil (VCO) with Raw Material of Coconut From Walennae Village, Sabbangparu District, Sengkang Regency - Side, Sumiati; Putri, Suriati Eka; Musa, Muhammad Iskandar (Indonesian Journal of Fundamental Sciences, 2023)
Coconut (Cocos nucifera L.) is a plant that provides many benefits to the rural economy. The part of coconut that has many benefits is the flesh of the fruit which can be taken from the coconut milk to make pure coconut oil which is commonly called Virgin Coconut Oil (VCO). In this study, the manufacture of VCO with the basic ingredients of old coconut from Walennae Village, Sabbangparu District, Sengkang Regency was carried out. This study aims to determine the characteristics of VCO in the form of peroxide number, Free Fatty Acid (FFA) number, and air content. The results showed the physical properties of the VCO produced, including the physical appearance of oil with a clear color, a distinctive aroma of oil, and no rancid smell. The results of the analysis of the chemical properties of the resulting VCO have a peroxidevalue of 1.5835 mg ek/kg; FFA number is 0.08% and water content is 0.18%.